2018
DOI: 10.3390/su10093066
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Humanities Students’ Perspectives on the Development and Sustainability of Artificial Intelligence (AI)

Abstract: This study investigates how the development of artificial intelligence (AI) is perceived by the students enrolled in technical and humanistic specializations at two universities in Timisoara. It has an emphasis on identifying their attitudes towards the phenomenon, on the connotations associated with it, and on the possible impact of artificial intelligence on certain areas of the social life. Moreover, the present study reveals the students’ perceptions on the sustainability of these changes and developments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 9 publications
3
21
0
Order By: Relevance
“…For factors associated with perceptions of the impact of HLMI regarding various dimensions, previous studies suggested gender and study area might play a crucial role [24], and this observation was supported by this study. Furthermore, in addition to gender and study area, results of this study also found CS expertise to be a significant predictor in many cases, as shown in Table 4.…”
Section: Rq1supporting
confidence: 88%
See 2 more Smart Citations
“…For factors associated with perceptions of the impact of HLMI regarding various dimensions, previous studies suggested gender and study area might play a crucial role [24], and this observation was supported by this study. Furthermore, in addition to gender and study area, results of this study also found CS expertise to be a significant predictor in many cases, as shown in Table 4.…”
Section: Rq1supporting
confidence: 88%
“…Even though there is a general "timing optimism" that AGI is to be achieved in the near future [1][2][3]7], extant literature that has looked into how people assess its overall impact have suggested mixed feelings, by experts and by university students alike [2,3,24]. The purposes of this present study were two-fold: first, to expand their findings by investigating how 562 Taiwanese university students perceived the overall impact of HLMI in three areas: one for human professions, with a set of 12 professions serving as indicators, and two for AI applications related to autonomous vehicles and to smart homes; and, secondly, to explore the predictors for these perceptions, especially for autonomous vehicles and smart homes, which had more empirical evidence to rely on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On that very point, Gherhes and Obrad [188] report the findings of their study on technical and humanities student perspectives on the development and sustainability of AI. The study discloses that out of 928 participants 58.3% considers that AI will have a positive influence on the society.…”
mentioning
confidence: 99%
“…On the other hand, the percentage of those confessing to being confused or concerned is also quite significant (41.7%). The probability that AI might destroy humankind and replace people in certain activities and jobs are among the greatest fears [188].…”
mentioning
confidence: 99%